Association between current medication use and progression of radiographic knee osteoarthritis: data from the Osteoarthritis Initiative - Perry, TA; Wang, X; Nevitt, M; Abdelshaheed, C; Arden, N; Hunter, DJ (Oxford University Press, 2021)
Objective Use of specific medications may accelerate the progression of radiographic knee osteoarthritis (RKOA). Our aim was to examine the effect of medication use on the progression of RKOA. Methods We used longitudinal data from the Osteoarthritis Initiative (OAI); an observational study of risk factors for knee OA. At baseline, we selected participants with RKOA (KL grade ≥2) and excluded those with a history of knee-related injury/surgery and other musculoskeletal disorders. Current medication use (use/non-use in the previous 30 days) and radiographic medial minimum joint space width (mJSW) data were available at baseline and annually up to 96-months follow-up. We used random-effects, panel-regression to assess the association between current medication use (non-users as reference group) and change in mJSW. Results Of 2,054 eligible participants, 2,003 participants with baseline mJSW data were included (55.7% female, mean age 63.3 (SD 8.98) years). Of 7 medication classes, at baseline non-steroidal anti-inflammatory drugs (NSAIDs) were the most frequently used analgesia (14.7%), anti-histamine (10.4%) use were frequent and, the following comorbidity medications were used most frequently; i) statins (27.4%), ii) anti-hypertensives (up to 15.0%), iii) anti-depressant/anxiolytics/psychotropics (14.0%), iv) osteoporosis-related medication (10.9%) and v) diabetes-related medication (6.9%). Compared with current non-users, current use of NSAIDs was associated with a loss of mJSW (b = -0.042, 95% CI -0.08 to -0.0004). No other associations were observed. Conclusions In current users of NSAIDs, mJSW loss was increased compared with current non-users in participants with RKOA. Clinical trials are required to assess the potential disease-modifying effects of these medications.